Human Pasteurella multocida Infection with Likely Zoonotic Transmission from a Pet Dog, Spain - Fátima Abreu; Carlos Rodríguez-Lucas; M. Rosario Rodicio; Ana I. Vela; José Francisco Fernández-Garayzábal; Pilar S. Leiva; Fernando Cuesta; Dolores Cid; Javier Fernández (Emerging Infectious Diseases, 2018)
We report a case of urinary tract infection caused by an unusual genotype (sequence type 211) of Pasteurella multocida associated with human infection. Molecular genetic analysis of P. multocida isolates obtained from the human patient and his pet strongly suggests a zoonotic transmission of this bacterium.